Low-methane forages: Discovery, development, and preparation for deployment in the Global South - Marin, Alejandra; Wenzl, Peter; Habte, Ermias; Jones, Chris; Arndt, Claudia; Rischkowsky, Barbara; Costa Junior, Ciniro; Muetzel, Stefan; Jaramillo, Andrés; Ku Vera, Juan Carlos; Makkar, Harinder; Chavarriaga, Paul; et al. (2025)
Food systems are responsible for approximately 60% of anthropogenic methane (CH₄) emissions; livestock contributes half. Reducing enteric methane emissions is a crucial strategy in addressing climate change as CH₄ is a more potent greenhouse gas than carbon dioxide (CO2). One way to reduce CH₄ emissions from the digestive process of ruminant animals is by identifying and developing low-methane forages (LMF). Forages, including browses, legumes and grasses containing anti-methanogenic compounds (AMC), such as tannins, saponins, flavonoids, H2-sinks, or methanogenesis inhibitors, constitute LMF. These offer a potentially cost-effective solution for reducing CH₄ production from livestock systems, whilst maintaining or improving productivity.  An international collaborative project among the three CGIAR Centers (Alliance Bioversity-CIAT, ICARDA, ILRI) and two specialized research laboratories (AgResearch, New Zealand and; Universidad Javeriana, Colombia) is focusing on three key areas: (1) identifying and promoting the use of LMF into ruminant production systems in the Global South; (ii) adding a CH₄ emission-reducing trait into widely used forage cultivars using conventional or precision breeding (gene-editing) approaches; and (iii) deploying LMF into forage-based livestock (ruminant) systems in the Global South.  Results from a pilot study on in vitro gas and CH₄ production identified several promising forage accessions with low to moderate CH₄ production relative to dry matter digestibility. In 2024, a total of 407 forage materials were assembled by the three CGIAR Centers and grown in the field for in vitro screening. Initial metabolomic analyses have advanced toward developing and deploying an HPLC-MS data analysis pipeline to streamline the identification, and annotation of metabolites. A protocol for genetic transformation of forage grass Urochloa humidicola (CIAT 16888) has been developed to facilitate gene-editing. Rumen microbiome studies are envisaged to understand rumen microbial ecology.  At the Colombia campus of the Alliance, 16 respiration chambers were constructed, eight of them tailored for large ruminants and eight for small ruminants. This specialized infrastructure will play a crucial role in validating in vivo any promising forages identified through in vitro screening, to support their subsequent scaling for broader applications. At ICARDA's Marchouch station in Morocco, significant progress has been made in developing a similar infrastructure for small ruminants. The ILRI team is using the existing respiration chambers for in vivo CH4 measurements while complementing these measurements with sulfur hexafluoride (SF6) methodology.  Ongoing efforts include developing LMF-specific emission factors, designing cost-effective MRV systems, and deploying climate finance mechanisms aimed at streamlining broad adoption of LMF. The LMF project contributes to the aims of Enteric Fermentation Research and Development Accelerator of the Global Methane Hub. These initiatives represent significant progress in aligning data-driven approaches with practical tools to improve greenhouse gas accounting, enhance livestock productivity, and support sustainable land management strategies under diverse agroecological contexts.